Safety and efficacy of Bergazym® P100 (endo‐1, 4‐β‐xylanase) as a feed additive for other birds for fattening, ornamental birds and other growing Suidae. (24th July 2019) - ,; Bampidis, Vasileios; Azimonti, Giovanna; de Lourdes Bastos, Maria; Christensen, Henrik; Dusemund, Birgit; Kouba, Maryline; Kos Durjava, Mojca; López‐Alonso, Marta; López Puente, Secundino; Marcon, Francesca; Mayo, Baltasar; et al.
Abstract: Following a request from the European Commission, the Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) was asked to deliver a scientific opinion on the safety and efficacy of Bergazym ® P100 (endo‐1, 4‐β‐xylanase, produced by a non‐genetically modified strain of Trichoderma reesei ) as a feed additive for other birds for fattening, ornamental birds and other growing Suidae. Considering the high margin of safety observed in the tolerance studies in chickens for fattening and in weaned piglets, and that the recommended level is the same, the Panel extrapolates the conclusions reached in chickens for fattening to all poultry species for fattening and ornamental birds and extrapolates the conclusions reached in weaned piglets to other growing Suidae species. Therefore, Bergazym ® P100 containing endo‐1, 4‐β‐xylanase as active substance is considered safe in other birds for fattening, ornamental birds and other growing Suidae at the recommended dose of 1, 500 EPU/kg feed. The additive is considered safe for the consumer and the environment. The additive is not irritant to the eyes and the skin, but it is considered a potential skin and respiratory sensitiser. The additive has the potential to be efficacious as a zootechnical additive, functional group 'digestibility enhancers', in other birds for fattening, ornamental birds and other growing Suidae at the recommended dose of 1, 500 EPU/kg feed.